Inisiasi Gerakan Desa Keluarga Aktif: Initiation of the Active Family Village Movement - Ramli, Ramli; Saleh, Adnan Achiruddin (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Family involvement in the mentoring process is a necessity. The family needs to be placed as the actor or subject. Families design forms of assistance because their basic needs are understood by the family. The family should not be placed as an object that merely receives coaching. The purpose of the community service program consists of two, namely first to initiate an active family village, and second to foster a Blessed, Safe, and Happy family based on Islamic psychology and culture. This service program uses the Sustainable Livelihood Approach (SLA) approach. This approach allows the family as an actor to design a service program. Active family involvement in every activity process. Data collection was carried out using the Participatory Rural Appraisal (PRA) method. Data was collected through a Focus Group Discussion (FGD) process and using a family schedule tool. The results of the program show that firstly the formation of four family development cadre structures, namely Old Age cadres, Youth Family Development Cadres, Integrated Service Post Cadres, and Toddler Family Development Cadres, secondly active family coaching through parenting assistance children through discussion of family goals, family and child needs, the child's personality structure in the perspective of Islamic-Bugis psychology.